Local Political Dynasty Of Saring Sungai Binjai Village Kusan Hilir Sub-District, Tanah Bumbu Regency - Zuhriyati, Erni; Putra, Bahrul Azis Pratama (Journal of Governance and Public Policy, 2021)
This research explains what factors have made the political dynasty of the Anafson Hadi family to survive to this day. Three variables are used to analyze this case, namely: political opportunity, internal influence, and external influence. By using qualitative research methods, this study shows that the factor of experience is not a consideration for society in making choices, but that educational factors are superior to the average community, political networks and economic capital are quite capable, then also history and culture that make the dynasty. Anafson Hadi still exists today.